2018
DOI: 10.1111/srt.12436
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkle and roughness measurement by the Antera 3D and its application for evaluation of cosmetic products

Abstract: The Antera 3D demonstrated its relevance for cosmetic product evaluation. We also provide recommendations for the analysis based on our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 19 publications
(27 reference statements)
1
44
0
Order By: Relevance
“…This would suggest that the Antera 3D pore measurements discriminate different severity of pores, similarly to the DermaTOP, rather than the Visia Complexion Analysis . These correlations were nevertheless of lower amplitude compared to texture and wrinkle parameters previously reported between the Antera 3D and the DermaTOP, which could be imputable to distinct thresholds for pore detection in the skin . No correlations were seen between pore visibility from image analysis on parallel polarized photographs and the Antera 3D, confirming once again that the technology within the instrument is closer to 3D instruments rather than pseudo‐relief techniques …”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…This would suggest that the Antera 3D pore measurements discriminate different severity of pores, similarly to the DermaTOP, rather than the Visia Complexion Analysis . These correlations were nevertheless of lower amplitude compared to texture and wrinkle parameters previously reported between the Antera 3D and the DermaTOP, which could be imputable to distinct thresholds for pore detection in the skin . No correlations were seen between pore visibility from image analysis on parallel polarized photographs and the Antera 3D, confirming once again that the technology within the instrument is closer to 3D instruments rather than pseudo‐relief techniques …”
Section: Discussionmentioning
confidence: 52%
“…As for the repeatability of the Antera 3D pore measurements from three successive acquisitions, the coefficients of variation (COV) were generally higher than colour or other topographic ones with many parameters exceeding 10%. Only Max Depth (all filters) and Mean pore volume/Mean pore area (Small and medium filters) showcased COV between 5 and 10%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A 1.1 mm filter was found to be optimal in excluding interference from the macro features and allowing precise targeting of the feature of interest. Previous studies have found correlation between DermaTOP and Antera 3D measurements when assessing other skin features . Congruently, a moderate correlation was detected between eyelid sagging feature volume (mm 3 ) as measured by the DermaTOP and Antera 3D at baseline before product application ( r = 0.544, P < .05).…”
Section: Discussionmentioning
confidence: 80%